Semen alkaline phosphatase activity reveals a lack of association with bull semen freezability - ALYETHODI, RAFEEQUE R; SIROHI, AJAYVIR SINGH; KARTHIK, S; TYAGI, S; SHARMA, ANKUR; PERUMAL, P; SUNDER, JAI; BHATTACHARYA, D (The Indian Journal of Animal Sciences, 2022)
The present study aimed to measure and comparealkaline phosphatase (ALP) enzyme activity in the bull’ssemen with varying freezability. Based on the post-thawmotility percentages, the bulls of similar age groups weregrouped into good and low freezable semen groups (Freezegroups).A total of 450 ejaculates from 21 bulls, with anaverage of 22 ejaculates per bull, were initially screened.Bulls (14) with similar initial motility and qualifyingminimum standard semen volume and sperm concentrationvalues were inducted in the final study. Consecutively twoto three ejaculates collected from each bull were processedfor alkaline phosphatase activity. Association of alkalinephosphatase activity with freezability was carried out usingan independent t-test. Correlations of alkaline phosphatasewith semen volume and sperm concentrations were assessedusing Pearson correlations. Alkaline phosphatase activityshowed an insignificant variation between freeze-groups.Further, no correlation of enzyme activity with the semenvolume and sperm concentration was observed. Besides,seminal plasma alkaline phosphatase activity assessed onconsecutive days of ejaculates showed no variation. Thepreliminary finding of this study indicates that alkalinephosphatase may not be involved in bull semen freezability.Hence, it may not be a reliable biochemical marker orindicator in bull cryopreservability studies.